3,3 '-Bithiophene - Costa, JCS (2010)
The title compound, C(8)H(6)S(2), is disordered [occupancy ratio = 0.839 (2):0.161 (2)] and sits across a centre of symmetry. In the crystal, the molecules are linked by a weak C-H center dot center dot center dot pi interaction.